Universal self-similar scaling of spatial Wilson loops out of equilibrium - Berges, Jürgen; Mace, Mark; Schlichting, Sören (Arxiv, 2017)
We investigate strongly correlated non-Abelian plasmas out of equilibrium. Based on numerical simulations, we establish a self-similar scaling property for the time evolution of spatial Wilson loops that characterizes a universal state of matter far from equilibrium. Most remarkably, it exhibits a generalized area law which holds for sufficiently large ratio of spatial area and fractional power of time. Performing calculations also for the perturbative regime at higher momenta, we are able to characterize the full nonthermal scaling properties of SU(2) and SU(3) symmetric plasmas from short to large distance scales in terms of two independent universal exponents and associated scaling functions.
Gesehen am 22.11.2017